Transcranial Direct Current Stimulation for Parkinson's Disease: A Systematic Review and Meta-Analysis - Liu, Xiang; Liu, Huiyu; Liu, Zicai; Rao, Jinzhu; Wang, Jing; Wang, Pu; Gong, Xiaoqian; Wen, Youliang (Frontiers in Aging Neuroscience, 2021)
Background: Parkinson's disease is a common neurodegenerative disorder with motor and non-motor symptoms. Recently, as adjuvant therapy, transcranial direct current stimulation (tDCS) has been shown to improve the motor and non-motor function of patients with Parkinson's disease (PD). This systematic review aimed to evaluate the existing evidence for the efficacy of tDCS for PD. We included English databases (PubMed, the Cochrane Library, Embase, and Web of Science) and Chinese databases [Wanfang database, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and China Biology Medicine (CBM)] without restricting the year of publication. Twenty-one tDCS studies, with a total of 736 participants, were included in the analysis. Two independent researchers extracted the data and characteristics of each study. There was a significant pooled effect size (−1.29; 95% CI = −1.60, −0.98; p < 0.00001; I2 = 0%) in the Unified PD Rating Scale (UPDRS) I and the Montreal cognitive assessment (SMD = 0.87, 95% CI = 0.50 to 1.24; p < 0.00001; I2 = 0%). The poor effect size was observed in the UPDRS III scores (SMD = −0.13; 95% CI = −0.64, 0.38; p = 0.61; I2 = 77%), and similar results were observed for the timed up and go (TUG) test, Berg balance scale, and gait assessment. The results of this meta-analysis showed that there was insufficient evidence that tDCS improves the motor function of patients with PD. However, tDCS seemed to improve their cognitive performance. Further multicenter research with a larger sample size is needed. In addition, future research should focus on determining the tDCS parameters that are most beneficial to the functional recovery of patients with PD.